AdaDeep: Adaboost and Deep Learning to Discover Student 5.0 AI Capabilities in the Fifth Industrial Revolution (Industry 5.0) - Yahya Almurtadha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
While industry 5.0 is a human-centered shift that focuses on the integration of cutting-edge technology with human skills and talent, Education 5.0 is a result of the substantial influence of the Industry 5.0 and Society 5.0 on education. In this study, we coin the term Student 5.0, a generation that learns skills that are becoming more and more crucial in the modern workplace as a consequence of merging the features of Industry 5.0 and Education 5.0. This study proposes combining two powerful prediction models: Adaboost and deep learning to form AdaDeep. AdaDeep prediction analysis was used on a student data set to discover the AI capabilities that students should acquire to thrive in the Industry 5.0 era. The goal is to gain insight into how the human centralization feature of industry 5.0 could assist in making improvements to the educational process. The findings of this study suggests that the reinforcement of the use of AI and individualized learning is what characterizes this new era of personalized and efficient education. In addition, Education 5.0 has increased the focus on Industry 5.0 soft skills like critical thinking, cooperation, and the ability to communicate effectively with both humans and machines (robots). To better prepare students for the job market, educational institutions should incorporate these abilities into the curriculum.